Reliability and diffusion-controlled through thickness oxidation of optical materials in LED-based products. (November 2017) - Yazdan Mehr, M.; Toroghinejad, M.R.; Karimzadeh, F.; van Driel, W.D.; Zhang, G.Q.
Abstract: In this study the temperature-induced oxidation reaction in bisphenol A polycarbonate (BPA-PC), leading to discoloration of the polymer used in solid state lighting applications, is studied. BPA-PC plates used as optical material in LED-based products suffer from yellowing and discoloration during service, resulting in a gradual deterioration of optical performance of the product. Discoloration reaction is greatly influenced by the temperature-induced oxidation of the polymer. In this study BPA-PC plates are aged at elevated temperature of 100–140 °C for a period up to 3000 h, aiming for accelerated oxidation of the plates. Diffusion of oxygen through the aged sample is studied up to 40 μm. A significant oxygen uptake is observed up to 20 μm. Activation energy of oxygen diffusion is measured to be 0.25 eV, which is close to activation energy of degradation reaction, reported in our previous works. Highlights: Increasing the exposure time is associated with the discolouration, loss of optical properties. The increase in the intensities at 1840 cm − 1 of degraded specimens confirms the diffusion-controlled oxidation reactions. Temperature-induced oxidation of BPA-PC is a surface reaction, up to depth 20 μm from the surface.